The Added Value of 18-Fluorodeoxyglucose-Positron Emission Tomography in the Diagnosis of the Behavioral Variant of Frontotemporal Dementia. (November 2014) - Kerklaan, B. J.; van Berckel, B. N. M.; Herholz, K.; Dols, A.; van der Flier, W. M.; Scheltens, P.; Pijnenburg, Y. A. L.
Characteristic frontotemporal abnormalities on structural or functional neuroimaging are mandatory for a diagnosis of probable behavioral variant of frontotemporal dementia (bvFTD) according to the new criteria. 18-Fluorodeoxyglucose-positron emission tomography (18F-FDG-PET) imaging is commonly reserved for patients with suspected bvFTD without characteristic structural neuroimaging results. We studied the diagnostic value of 18F-FDG-PET in these patients. Methods: The 18F-FDG-PET was performed in 52 patients with suspected bvFTD but lacking characteristic structural neuroimaging results. The clinical diagnosis of bvFTD in the presence of functional decline (bvFTD/fd+) after a follow-up period of 2 years was used as a golden standard. Results: The sensitivity of 18F-FDG-PET for bvFTD/fd+ was 47% at a specificity of 92%. The differential diagnosis comprised alternative neurodegenerative and psychiatric disorders and a benign phenocopy of bvFTD. Conclusions: The 18F-FDG-PET is able to identify nearly half of the patients with bvFTD who remain undetected by magnetic resonance imaging. In our selected group, high specificity enables exclusion of psychiatric and other neurodegenerative disorders.